Community conflicts and their management mechanisms - Boronova Khilola Akramjanovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
Conflict is a state or conflict of attitudes, opinions, views, values, interests, goals, needs of opponents, which arises in the solution of certain personal, professional, social issues. Conflict is a specific person or group. that there is no compromise between two or more parties. Each side seeks to gain its own point of view, preventing the other side from doing so. Conflict is often equated with aggression, threat, debate, hostility, war, etc., and is always perceived as an undesirable event that needs to be avoided as much as possible, or resolved as soon as it arises. This attitude towards conflict is reflected in the works of the authors of the “scientific school” and the “school of administration”. The authors of the school of “human relations” also believed that conflicts could be avoided. They saw the conflict as a sign of inefficiency and poor management. They believed that a good relationship in the company could prevent conflicts